Torso height optimization for bipedal locomotion. (25th October 2018) - Hildebrandt, Arne-Christoph; Ritt, Konstantin; Wahrmann, Daniel; Wittmann, Robert; Sygulla, Felix; Seiwald, Philipp; Rixen, Daniel; Buschmann, Thomas
Bipedal robots can be better alternatives to other robots in certain applications, but their full potential can only be used if their entire kinematic range is cleverly exploited. Generating motions that are not only dynamically feasible but also take into account the kinematic limits as well as collisions in real time is one of the main challenges towards that goal. We present an approach to generate adaptable torso height trajectories to exploit the full kinematic range in bipedal locomotion. A simplified 2D model approximates the robot's full kinematic model for multiple steps ahead. It is used to optimize the torso height trajectories while taking future motion kinematics into account. The method significantly improves the robot's motion not only while walking in uneven terrain, but also during normal walking. Furthermore, we integrated the method in our framework for autonomous walking and we validated its real-time character in successfully conducted experiments.